2018
DOI: 10.1126/science.aat2975
|View full text |Cite
|
Sign up to set email alerts
|

Key-and-lock commodity self-healing copolymers

Abstract: Self-healing materials are notable for their ability to recover from physical or chemical damage. We report that commodity copolymers, such as poly(methyl methacrylate)/n-butyl acrylate [p(MMA/nBA)] and their derivatives, can self-heal upon mechanical damage. This behavior occurs in a narrow compositional range for copolymer topologies that are preferentially alternating with a random component (alternating/random) and is attributed to favorable interchain van der Waals forces forming key-and-lock interchain j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
240
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(271 citation statements)
references
References 35 publications
(22 reference statements)
9
240
0
3
Order By: Relevance
“…Polymers that undergo autonomous healing are mimicking intrinsic properties of biosystems and are highly desirable for many applications because they can endow materials with the capability to repair mechanical damage. [1] To realize selfhealing properties, some strategies have been developed, especially using dynamic reversible noncovalent transformations to induce the reformation of damaged interfaces. [2][3][4][5][6][7] Taking advantage of the supramolecular toolbox that is, Hbonds, [2] host-guest combinations, [3] metal-ligand interactions, [4] ionic bonds, [5] dynamic covalent bonds, [6] dipoledipole interactions, [7] and even van der Waals force, [1e] have shown to be versatile features in the design of self-healing gels and polymers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Polymers that undergo autonomous healing are mimicking intrinsic properties of biosystems and are highly desirable for many applications because they can endow materials with the capability to repair mechanical damage. [1] To realize selfhealing properties, some strategies have been developed, especially using dynamic reversible noncovalent transformations to induce the reformation of damaged interfaces. [2][3][4][5][6][7] Taking advantage of the supramolecular toolbox that is, Hbonds, [2] host-guest combinations, [3] metal-ligand interactions, [4] ionic bonds, [5] dynamic covalent bonds, [6] dipoledipole interactions, [7] and even van der Waals force, [1e] have shown to be versatile features in the design of self-healing gels and polymers.…”
mentioning
confidence: 99%
“…However, there remain some very challenging issues facing the design of a self-healing supramolecular network: i) The introduction of weak but reversible noncovalent bonds into the network usually decreases significantly the stiffness of the network, leading to a self-healing but soft network; ii) The introduction of noncovalent bonds, especially based on hierarchical multi-component systems often requires complex synthetic procedures increasing material costs; iii) Many self-healing polymers contain or involve external solvents to support the supramolecular recognition processes, while developing self-healable dry polymers is more preferable for industrial application. [1,2,8] Very recently, our lab developed an unprecedented supramolecular polymer using the natural small molecule, [8] thioctic acid (TA), as the main feedstock. A crosslinked solid polymer was obtained by a facile co-mixing method of molten TA liquid, 1,3-diisopropenylbenzene (DIB) and minimal FeCl 3 , involving no external solvent.…”
mentioning
confidence: 99%
“…[17] This drives us to explore an available route to develop PCs with large-area crack-free by using relatively soft monomers. That is highly ascribed to the easy production of uniform monodispersed colloids by these monomers.However,the glass transition temperatures of PS and PMMA are 100 8 8C, 105 8 8C, respectively,w hich are much higher than their corresponding film forming temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Thus,t he film cracks may easily occur during film forming process.O nt he contrary,t he soft monomer butyl acrylate (BA) mixed with hard monomers could construct perfect PC films with large area crack-free.B ut it may be impossible to produce PBA( T g = À54 8 8C) PCs alone because the soft BA monomer cannot form homogeneous emulsion particles. [17] This drives us to explore an available route to develop PCs with large-area crack-free by using relatively soft monomers.…”
Section: Introductionmentioning
confidence: 99%
“…These observations have triggered research on artificial self-healing materials, aiming to improve the materials adopted in civil and structural engineering, with a potentially significant impact on many practical applications. From the seminal work of White et al [4], by now many techniques have been introduced to design and manufacture artificial self-healing materials [5][6][7][8][9][10][11][12][13][14]. A comprehensive review can be found in references [15][16][17].…”
Section: Introductionmentioning
confidence: 99%